Differential AMPK-mediated metabolic regulation observed in hibernation-style polymorphisms in Siberian chipmunks - Kamata, Taito; Yamada, Shintaro; Sekijima, Tsuneo (Frontiers in Physiology, 2023)
Hibernation is a unique physiological phenomenon allowing extreme hypothermia in endothermic mammals. Hypometabolism and hypothermia tolerance in hibernating animals have been investigated with particular interest; recently, studies of cultured cells and manipulation of the nervous system have made it possible to reproduce physiological states related to hypothermia induction.However, much remains unknown about the periodic regulation of hibernation. In particular, the physiological mechanisms facilitating the switch from an active state to a hibernation period, including behavioral changes and the acquisition of hypothermia tolerance remain to be elucidated. AMPK is a protein known to play a central role not only in feeding behavior but also in metabolic regulation in response to starvation. Our previous research has revealed that chipmunks activate AMPK in the brain during hibernation. However, whether AMPK is activated during winter in non-hibernating animals is unknown. Previous comparative studies between hibernating and non-hibernating animals have often been conducted between different species, consequently it has been impossible to account for the effects of phylogenetic differences. Our long-term monitoring of siberian chipmunks, has revealed intraspecific variation between those individuals that hibernate annually and those that never become hypothermic. Apparent differences were found between hibernating and non-hibernating types with seasonal changes in lifespan and blood HP levels. By comparing seasonal changes in AMPK activity between these polymorphisms, we clarified the relationship between hibernation and AMPK regulation.In hibernating types, phosphorylation of p-AMPK and p-ACC was enhanced throughout the brain during hibernation, indicating that AMPK-mediated metabolic regulation is activated. In nonhibernating types, AMPK and ACC were not seasonally activated. In addition, AMPK activation in the hypothalamus had already begun during high Tb before hibernation. Changes in AMPK activity in the 3 brain during hibernation may be driven by circannual rhythms, suggesting a hibernation-regulatory mechanism involving AMPK activation independent of Tb. The differences in brain AMPK regulation between hibernators and non-hibernators revealed in this study were based on a single species thus did not involve phylogenetic differences, thereby supporting the importance of brain temperatureindependent AMPK activation in regulating seasonal metabolism in hibernating animals.